Consumer behavior : building marketing strategy - Hawkins, Del I.; Mothersbaugh, David L. (Boston : McGraw-Hill Irwin, 2010)
This book is a strategic look at consumer behavior in order to guide successful marketing activities. The Wheel of Consumer Analysis is the organizing factor in the book. The four major parts of the wheel are consumer affect and cognition, consumer behavior, consumer environment, and marketing strategy.
Part One: Introduction Chapter One: Consumer Behavior and Marketing Strategy Part Two: External Influences Chapter Two: Cross-Cultural Variations in Consumer Behavior Chapter Three: The Changing American Society: Values Chapter Four: The Changing American Society: Demographics and Social Stratification Chapter Five: The Changing American Society: Subcultures Chapter Six: The American Society: Families and Households Chapter Seven: Group Influences on Consumer Behavior Part Two Cases: Cases 2-1 through 2-9 Part Three: Internal Influences Chapter Eight: Perception Chapter Nine: Learning, Memory, and Product Positioning Chapter Ten: Motivation, Personality, and Emotion Chapter Eleven: Attitudes and Influencing Attitudes Chapter Twelve: Self-Concept and Lifestyle Part Three Cases: Cases 3-1 through 3-10 Part Four: Consumer Decision Process Chapter Thirteen: Situational Influences Chapter Fourteen: Consumer Decision Process and Problem Recognition Chapter Fifteen: Information Search Chapter Sixteen: Alternative Evaluation and Selection Chapter Seventeen: Outlet Selection and Purchase Chapter Eighteen: Postpurchase Processes, Customer Satisfaction, and Customer Commitment Part Four Cases: Cases 4-1 through 4-8 Part Five: Organizations as Consumers Chapter Nineteen: Organizational Buyer Behavior Part Five Cases: Cases 5-1 through 5-2 Part Six: Consumer Behavior and Marketing Regulation Chapter Twenty: Marketing Regulation and Consumer Behavior Part Six Cases: Cases 6-1 through 6-2 Appendix A: Consumer Behavior Research Methods Appendix B: Consumer Behavior Audit.
Includes bibliographical references and index.
Keywords: Consumer behavior -- United States; Market surveys -- United States; Consumer behavior -- United States -- Case studies